THEORETICAL STUDIES ON POSSIBLE SULFUR OXIDES WITH + 2 OXIDATION STATES IN AQUEOUS SOLUTION - Tossell J.A. (My University, 1997)
In the oxidation of sulfide to sulfate a number of different intermediate products are commonly observed, but products with S oxidation states of + 2 seem generally to be absent. Recently Vairavamurthy and Zhou (hereafter VZ) [Vairavamurthy, M.A., Zhou, W., 1995. Characterization of a transient + 2 sulfur oxidation state intermediate from the oxidation of aqueous sulfide. In: Vairavamurthy, M.A., Schoonen, M.A.A. (Eds.), Geochemical Transformations of Sedimentary Sulfur. ACS Symposium Ser., 612, ACS, Washington, DC, pp. 280-292] characterized an intermediate oxidation state sulfur oxide whose concentration increased during the early stages of sulfide oxidation and then declined. On the basis of IR and XANES spectra they formulated this as SO-22, with the sulfur in oxidation state + 2. Steiger and Steudel [Steiger, T., Steudel, R., 1992. Sulphur compounds. Part 149. Structures, relative stabilities and vibrational spectra of several isomeric forms of sulphoxylic acid (H2SO2) and its anion (HSO-12): an ab initio study. J. Molec. Struct. (THEOCHEM) 257, 313-323] had earlier studied theoretically the species (OH)SO-1, which had a strong S=O IR absorption near the energy observed by VZ for the + 2 oxidation state intermediate, but which was calculated to be of higher energy (in the gas phase) than its isomer HSO-12 (with the H bonded to S). We have calculated the relative energies and the vibrational spectra of (OH)SO-1 and HSO-12 coordinated to four water molecules, establishing that the O-H form, i.e. (OH)SO-1, is more stable than the S-H form in the presence of small numbers of waters (we find a similar result for the O-H and S-H isomers of the bisulfite anion) and that the calculated S=O stretching frequency for (OH)SO-1 in the presence of water is still very close to that observed by VZ (about 911 cm-1 calculated vs. 918 cm-1 experimental). The calculated S-OH stretching frequency in (OH)SO-1 is around 690 cm-1, and thus could not have been observed in water solution by VZ. XANES energies have also been estimated from ground state orbital energies for (OH)SO-1 and a range of other sulfur oxides, establishing that the XANES of (OH)SO-1 falls into the range observed for the + 2 oxidation state intermediate by VZ. The IR and XANES evidence and the calculated relative stabilities are thus consistent with the assignment of this species as (OH)SO-1. To more completely characterize this and related species we have also calculated their 17O NMR spectra, which we find to depend in a fairly complicated way on S oxidation state, coordination number and degree of protonation. For the (OH)SO-1 species in solution we predict 17O NMR shifts of 63 (compared to gas-phase H2O) for the O-H oxygen and 92 for the unprotonated O, both considerably more shielded than either (OH)SO-12 or S2O-23. S oxides with more negative oxidation states, e.g. SO-2, show more shielded 17O NMR signals and lower vibrational energies. The reaction of SH- + O2 to give (OH)SO-1 is calculated to be slightly endothermic in solution while the reaction of (OH)SO-1 to give thiosulfate is strongly exothermic.
Keywords: SULFIDE; SULFATE; OXIDATION; IR; XANES; MOLECULAR ORBITAL